Competitive ability of different weed species - S.M. Rezaul Karim (ANSInet, 2002)
A range of weed species were grown in all combinations with four crop species (wheat, barley, bean and oilseed rape) under field conditions of 1990-91. The weeds were ranked on the basis of their competitive abilities. The degree to which competitive ability was specific to particular combination of crops and weed species was examined. Two indices-crop equivalent and aggressivity were compared to measure the competitive ability of the weeds. Based on aggressivity the ranking order of the weeds for their competitive abilities was, cleavers (Galium aparine L.)> wild oats (Avena fatua L.)> field speedwell (Veronica persica Poir.)> common chickweed (Stellaria media L. Cyrill.)> scented mayweed (Matricaria recutita). The ranking of the weeds varied depending on the associated crop and at different growth stages. There was a poor correlation between crop equivalent and aggressivity.